The Boer War - Van Hartesveldt, Fred R. (Gloucestershire : Sutton Pub., 2000)
The history of the Boer War is traced here, from its origins in national ambition, through the sieges of Ladysmith, Kimberley and Mafeking to the horrors of the British concentration camps and the eventual peace.
Includes bibliographical references (pages 110-114) and index.
Keywords: 1899-1902; South African War, 1899-1902.; Guerre des Boers, 1899-1902.